Correction: Babaeian et al. Future Projection of Drought Vulnerability over Northeast Provinces of Iran during 2021–2100. Atmosphere 2021, 12, 1704 - Iman Babaeian; Atefeh Erfani Rahmatinia; Alireza Entezari; Mohammad Baaghideh; Mohammad Bannayan Aval; Maral Habibi (Atmosphere, 2022)
Error in Figure Legend [...]